A proteção autoral dos jogos eletrônicos no Brasil : análise dos elementos visuais no caso Zynga V. Vostu - Recena, Martina Gaudie Ley (2020)
This paper aims to present the concepts of copyright requirements - originality and expression - as well as legal limitations. This approach encompasses the Brazilian and US systems, because of its vast experience in addressing the copyright of video games, and lastly to study a case involving alleged copyright infringement over visual elements of the game, involving a US company and a Brazilian company. Because of this analysis, originality was defined as creation, which is always new and endowed with a minimum of creativity, and creativity will always have the author’s individuality. Regarding the expression, it has been established that copyright does not protect the content of technical and scientific works, only the form adopted, that elements necessary for the expression of an ideas are not protected, that it is impossible to protect the format of a program and that there is possible to protect character. In analyzing the limitations on copyright, the most relevant were identified as the article 46, VIII of Law 9.610/98 and those in Article 6, III of Law 9.609/98. Concerning the United States, the current definition of originality is non-copying with a minimum of creativity, refuting the sweat of the brow doctrine. The AFC Test was presented, based on which the New Jersey District Court understood the possibility of protecting expressions related to the rules of the game and their functional aspects, provided that they are original. Fair use, merger doctrine and scénes à faire doctrine were explained. When analyzing the proposed case, it was realized that the closer to reality the objective game is, the lower the likelihood of copyright protection, since there is a very limited number of ways to express reality reliably. It was found that the merger doctrine and article 6, inc. VIII, of Law 9.609/98 has great applicability in the case. Concluding that the mere merging of elements in the public domain does not make the good copyrightable, it is necessary to add a new element and to express a minimum of creativity or, in the absence of such addition, that the composition of elements in a public domain is new and original.